SOYBEAN BIOESTER OBTAINED IN A BUBBLE COLUMN ESTERIFICATION REACTOR – A RHEOLOGICAL STUDY - BORAN, Sorina; TĂMĂȘ, Andra; MOȘOARCĂ, Giannin (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The paper presents the rheological characterization of a bio-ester with possible lubricant properties, obtained from soybean oil fatty acids. The rheological characterization was carried out under thermostatic conditions, using a Brookfield CAP2000+L viscometer in the characteristic domain of these fluids. The variation of the apparent viscosity ηa as a function of shear rate and the variation of the two indices (K and n) as a function of temperature were determined, as well as the flow activation energy, Ea from Arrhenius type equations. A rheological model was proposed.